PENGARUH HARGA DAN KUALITAS PELAYANAN PELANGGAN TERHADAP LOYALITAS PELANGGAN DI ALDI MOTOR TULANG BAWANG BARAT - Fajar Wahyudi; Ni Putu Rahayu (Program Studi Manajemen | Universitas Pasir Pengaraian, 2025)
Competition in the transportation industry is getting tighter. The purpose of this research is to carry out empirical testing on the effect of price and service quality on customer loyalty in a partial or simultaneous way on Aldi Motor Tulang Bawang Barat. This research was carried out through a quantitative approach technique in descriptive analysis using an analysis tool, namely SPSS. The tests that will be carried out are validity tests and reliability tests, then classical assumption tests, then multiple linear regression tests, t tests, F tests, and determination coefficient tests. The population in this study uses customers who came in the past week, which is 84 customers, then the minimum number of samples using the Slovin formula and the error rate of 5% results in a minimum sample number of 70 customers. The sample collection used is a simple random sampling technique. Data collection is carried out by means of an online questionnaire along with a Likert scale of 1-5. The findings of this study are that the price and quality of service have a positive and significant impact both partially and simultaneously.